2003
DOI: 10.1099/mic.0.25985-0
|View full text |Cite
|
Sign up to set email alerts
|

Cell line differences in bacterially translocated ExoS ADP-ribosyltransferase substrate specificity

Abstract: Exoenzyme S (ExoS) is an ADP-ribosyltransferase (ADPRT) directly translocated into eukaryotic cells by the type III secretory (TTS) process of Pseudomonas aeruginosa. Comparisons of the functional effects of ExoS on human epithelial and murine fibroblastic cells showed that human epithelial cells exhibited an overall increased sensitivity to the effects of bacterially translocated ExoS on cell proliferation, morphology and re-adherence. ExoS was also found to ADP-ribosylate a greater number of low-molecular-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 44 publications
6
32
1
Order By: Relevance
“…Recently, the ADP-ribosylation activity of ExoS has been linked to cellular adherence, the maintenance of filopodia, and enhanced lamellipodia and cellular ruffling (32). Different cell lines demonstrate different sensitivities to intoxication, with epithelial cells being the most affected by the action of ExoS (33). These data suggest that ExoS ADP-ribosylates an unidentified host protein(s) that is responsible for cytoskeletal changes and/or cell death.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…Recently, the ADP-ribosylation activity of ExoS has been linked to cellular adherence, the maintenance of filopodia, and enhanced lamellipodia and cellular ruffling (32). Different cell lines demonstrate different sensitivities to intoxication, with epithelial cells being the most affected by the action of ExoS (33). These data suggest that ExoS ADP-ribosylates an unidentified host protein(s) that is responsible for cytoskeletal changes and/or cell death.…”
mentioning
confidence: 80%
“…Rounding-Recent studies demonstrated that the ADP-r activity of ExoS leads to a loss of cellular adherence upon infection with P. aeruginosa (33). To quantify the effects of the ADP-r activity on cell morphology, HeLa cells were infected with P. aeruginosa expressing either the wild-type ExoS, ExoS deficient in GTPase-activating protein activity (R146K), ExoS deficient for ADP-r and GTPase-activating protein activity (R146K/E381D), or a vector (pUCP) control.…”
Section: Exos Adp-ribosyltransferase Activity Is Sufficient To Inducementioning
confidence: 99%
“…To summarize, infections by the opportunistic pathogen P. aeruginosa are influenced by host cell properties (6,41,51,52). Through visualization of ExoS translocation in relation to T24 cell migration, we were able to characterize the mechanisms underlying eukaryotic cell differences in T3S translocation caused by mutations that inactivate ExoS GAP or ADPRT activities.…”
Section: Discussionmentioning
confidence: 97%
“…The T24 cell model was chosen in this study to further investigate the role of the leading edge and cell migration in P. aeruginosa infections due to its highly migratory mesenchymal phenotype. Eukaryotic cell properties are known to influence ExoS GAP and ADPRT toxicity (51), which leads to predictions that alterations in cell migration properties might affect ExoS GAP and ADPRT toxicity. In this regard, recent studies using real-time phase-contrast imaging to examine the effects of ExoS on immortalized corneal epithelial cells found that infection with P. aeruginosa expressing ADPRT-active ExoS allowed P. aeruginosa to be internalized and replicate within membrane blebs (2).…”
Section: Discussionmentioning
confidence: 99%
“…Observations from this study showed that ExoS anti-internalization activity was mostly dependent on its ADPr activity which differs from previous studies in HeLa cells where the ExoS antiinternalization function was attributed to RhoGAP activity . One explanation for this discrepancy could be due to the use of a different cell line, and cell line properties are known to influence the substrate specificity of ExoS (Rucks, Fraylick et al 2003). The ability of ExoS ADPr, but not its RhoGAP activity, to inactivate Rab5 ( Figure 10A) provides evidence for cell-type dependent mechanisms of phagocytosis, which can be differentiated by ExoS.…”
Section: Discussionmentioning
confidence: 99%